Medicinal herbs and manufactured drugs: for treatment of COVID-19 and its complications in Aden -Yemen - Al-ashwal, Nashwan Saleh (Journal of medical and pharmaceutical sciences, 2021)
Aims: To detect the herbs benefits in treatment of COVID-19 patients. To discover the effect of coronavirus-2 on the clinical and subclinical diseases that has accompanied with/ or caused by H. pylori infection or vice versa.Results: A study of observational clinical trial with randomly selected patients, enrolled to it 775 patients; 35 of them, have suffered of chikungunya and dengue fevers, and the remaining 740 patients were of confirmed and highly suspected COVID-19 cases. They were divided into six groups; four of them have a manifestations of COVID-19 of confirmed and suspected cases, the 5th group was for patients with other viral causes; chikungunya and dengue fevers, and the sixth was a group of extra-pulmonary manifestations, and each one was subdivided into two subgroups except group D that was subdivided into three subgroups. The patients that were giving an Echinacea syrup had treated within 48 – 72 hours; clinically and para-clinically, earlier than the patients that were giving a combination of herbs; such as Curcuma, Ginger and Cissus rotundifolia whose had got a recovery after 7 days, while the patients that were giving clarithromycin tabs and Echinacea syrup had recovered earliest, i.e. after 24 hours, it achieved a highest percentage of success that reached 98%, 100% and 100% respectively, i.e. the medicinal substances of Echinacea purpura have an antiviral effect on CoV-2, that evidenced by the fast and complete cure of COVID 19 manifestations, if compared with the clinical effect of Remdesivir or hydroxychloroquine. The combination therapy; Echinacea syrup, Ginkgo biloba tabs and the H. pylori therapeutic and preventive program, has achieved a successful effect on patients’ illness of severe COVID-19 or those with accelerated or aggravated diseases that accompanied with/caused by H. pylori infection, in post covid-19 period. The patients with chikungunya and dengue fevers haven't responded to the Echinacea herbal therapy; i.e. Echinacea has no benefit in these two diseases but it has an efficient effect against COVID-19.Conclusion: This study proves the following: I) The medicinal extracts from Echinacea purpurea have an efficient effect against novel-CoV-2 disease, faster than Curcuma, Ginger and Cissus rotundifolia, but the Echinacea and clarithromycin have a fastest remedy from the COVID-19. II) The combination of Echinacea, H. pylori therapeutic and preventive program, and Ginkgo biloba, is a successful regime for treating of patients with severe Covid-19, and whose suffered of post covid-19 extra-pulmonary diseases, allowed them to return to their work after 7 days of treatment only "Inshaa Allah". III) Coronavirus-2 had accelerated the subclinical and aggravated the clinically apparent diseases that has accompanied with /caused by H. pylori infection.
Keywords: Covid-19; Echinacea; accelerated; H. pylori; Ginkgo biloba